2011
DOI: 10.1038/ncomms1329
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected layers of cryptic diversity in wood white Leptidea butterflies

Abstract: uncovering cryptic biodiversity is essential for understanding evolutionary processes and patterns of ecosystem functioning, as well as for nature conservation. As European butterflies are arguably the best-studied group of invertebrates in the world, the discovery of a cryptic species, twenty years ago, within the common wood white Leptidea sinapis was a significant event, and these butterflies have become a model to study speciation. Here we show that the so-called 'sibling' Leptidea actually consist of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
203
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(223 citation statements)
references
References 41 publications
13
203
2
Order By: Relevance
“…A proportionally great number of "double" (in one case triple) species have been identified by these methods and butterflies may be second only to amphibians, or sometimes mammals, in this respect. Porter et al 1997;Dapporto 2010;Dincă et al 2011aDincă et al , 2011bZinetti et al 2013), to cite some of the most recently demonstrated, do not fit well into the ESU paradigm. These species, irrespectively of their generally strong genetic differentiation, apparently show too little ecological distinctness, within the same pair, to allow us to classify them as separate ESUs.…”
Section: Basic Conceptmentioning
confidence: 99%
“…A proportionally great number of "double" (in one case triple) species have been identified by these methods and butterflies may be second only to amphibians, or sometimes mammals, in this respect. Porter et al 1997;Dapporto 2010;Dincă et al 2011aDincă et al , 2011bZinetti et al 2013), to cite some of the most recently demonstrated, do not fit well into the ESU paradigm. These species, irrespectively of their generally strong genetic differentiation, apparently show too little ecological distinctness, within the same pair, to allow us to classify them as separate ESUs.…”
Section: Basic Conceptmentioning
confidence: 99%
“…However, the analysis of mitochondrial and nuclear DNA markers of Leptidea genus by Dinca et al (2011) revealed that L. sinapis -L. reali, previously understood to be a cryptic pair, are really part of a triplet of species that also includes L. juvernica. Shtinkov et al (2016) …”
Section: Resultsmentioning
confidence: 99%
“…Based on that premise, the Indonesian Biodiversity Discovery and Information System Even in well studied areas, DNA barcoding has uncovered many cases of overlooked, misinterpreted, cryptic, or even new species (Dincă et al 2011, Hendrich et al 2014, Morinière et al 2014, Schmidt et al 2015. The Swedish Malaise trap program has so far increased the country's insect fauna by more than 1,900 species, including several hundred species new to science (Ronquist 2010, Karlsson 2017.…”
Section: Indobiosys -Dna Barcoding As a Tool For The Rapid Assessmentmentioning
confidence: 99%